2022
DOI: 10.3390/nano12193351
|View full text |Cite
|
Sign up to set email alerts
|

High Strength Die-Attach Joint Formation by Pressureless Sintering of Organic Amine Modified Ag Nanoparticle Paste

Abstract: Sintered silver (Ag) die-attach has attracted much attention in power systems with high power density and high operating temperature. In this paper, we proposed a novel surface modification method for Ag nanoparticles with organic amines as a coating agent for enhancing the pressureless sintering performance. This work systematically introduced the Ag nanoparticle modification process, Ag paste preparation, and sintering process and compared the changes in the sintering performance of Ag nanoparticles after mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The electronic binding energies of Ag 0 3d 5/2 for Ag/SiO 2 and Ag/Ph-SiO 2 were 368.1 and 368.4 eV, respectively, which confirmed that the precursor of silver salt had been totally converted to the form of metallic silver during the preparation process. , This is also consistent with the XRD characterization results. In addition, compared with that of Ag/SiO 2 , the peaks of Ag 0 3d 5/2 and Ag 0 3d 3/2 shifted to a higher binding energy for Ag/Ph-SiO 2 , indicating that the electron density of Ag NPs increased, which should be caused by the stronger interaction between Ag NPs and the surface of Ag/Ph-SiO 2 . The more negative metal could show a stronger catalytic hydrogenation ability, which is a potentially beneficial factor for the following catalytic hydrogenation application. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic binding energies of Ag 0 3d 5/2 for Ag/SiO 2 and Ag/Ph-SiO 2 were 368.1 and 368.4 eV, respectively, which confirmed that the precursor of silver salt had been totally converted to the form of metallic silver during the preparation process. , This is also consistent with the XRD characterization results. In addition, compared with that of Ag/SiO 2 , the peaks of Ag 0 3d 5/2 and Ag 0 3d 3/2 shifted to a higher binding energy for Ag/Ph-SiO 2 , indicating that the electron density of Ag NPs increased, which should be caused by the stronger interaction between Ag NPs and the surface of Ag/Ph-SiO 2 . The more negative metal could show a stronger catalytic hydrogenation ability, which is a potentially beneficial factor for the following catalytic hydrogenation application. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, compared with that of Ag/SiO 2 , the peaks of Ag 0 3d 5/2 and Ag 0 3d 3/2 shifted to a higher binding energy for Ag/Ph-SiO 2 , indicating that the electron density of Ag NPs increased, which should be caused by the stronger interaction between Ag NPs and the surface of Ag/Ph-SiO 2 . 41 The more negative metal could show a stronger catalytic hydrogenation ability, which is a potentially beneficial factor for the following catalytic hydrogenation application. 42−44 3.2.…”
Section: Acs Applied Nano Materialsmentioning
confidence: 99%
“…Currently, solder for new automotive power modules is made of tin-based compounds [3,4]. Because of its low melting temperature and degradation, tinbased solder is not suitable for supporting temperatures higher than 150 °C [5]. A replacement of such technology is urgently required to improve performance and reliability over the current solder process.…”
Section: Introductionmentioning
confidence: 99%
“…The research underscores the impact of nanoparticle proximity on optical rectification coefficients under various external field conditions, providing insights into the design and optimization of photonic materials and devices that exploit the unique electromagnetic interactions between nanoparticles and molecular systems. The experimental work of Shen et al [ 6 ] introduces a novel approach to enhancing the sintering performance of silver nanoparticle pastes through surface modification with organic amines. This method significantly improves the electrical conductivity and mechanical strength of sintered joints, providing a promising solution for high-performance electronic packaging applications.…”
mentioning
confidence: 99%